A prospective study of the management of open fractures of tibia - Mohammad, Abul Kalam; Shrivastav, Mahesh; Gupta, Pradeep; Sayed, Awais (Journal of Nobel Medical College, 2012)
A Prospective study of 30 cases of type III open fractures of tibia is conducted at Nepal Medical College, Kathmandu and Nobel Medical College, Biratnagar from 2009 to 2011. All cases included in the study were initially managed by wound debridement and external fixation, and followed-up regularly for 10 months for outcome. Five cases developed deep infection and 10 had superficial infection, which subsided with prolonged use of antibiotics. Union was obtained in 7to 8 months for 28 cases. Two cases resulted in non- union which had been managed by bone grafting. Open Type III fractures of tibia are still a difficult and challenging problem for orthopedic surgeons. Almost all cases are required for twice surgery including secondary closure, skin grafting and readjustment. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7295 Journal of Nobel Medical College (2012), Vol.1 No.2 p.25-28